2022
DOI: 10.3389/fneur.2022.823611
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Glucose Index Is Related to Carotid Plaque and Its Stability in Nondiabetic Adults: A Cross-Sectional Study

Abstract: BackgroundCarotid plaque plays an important role in the development of stroke. The triglyceride-glucose (TyG) index is a reliable alternative marker of insulin resistance. However, there are limited data regarding the relationship between TyG index and carotid plaque and its stability in nondiabetic adults.MethodsThis study was carried out on 24,895 urban workers (10,978 men and 13,917 women) aged 20 years or older who participated in a comprehensive health screening between January 2016 and December 2017 at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Third, insulin resistance is an independent predictor for development of antiplatelet drug resistance which leads to the failure of secondary stroke prevention in a large proportion of stroke patients [7,23]. Finally, TyG index is related to other vascular risk factors such as unstable carotid plaques which might also lead to recurrent ischemic stroke [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, insulin resistance is an independent predictor for development of antiplatelet drug resistance which leads to the failure of secondary stroke prevention in a large proportion of stroke patients [7,23]. Finally, TyG index is related to other vascular risk factors such as unstable carotid plaques which might also lead to recurrent ischemic stroke [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Triglyceride-glucose (TyG) index, denoted ln [triglycerides (TG) (mmol/L) * fasting blood glucose (FBG) (mmol/L)/2], is a simple and reliable surrogate marker of insulin resistance [9]. Many previous studies have shown an association between a higher TyG index and an increased incidence of atherosclerosis, intima media thickness of common carotid artery, unstable carotid plaque, hypertension, arterial stiffness, and cardiovascular disease [10][11][12][13]. As expected, a plenty of evidences proved that TyG index was independently associated with the occurrence of stroke, and a higher TyG index was also a predictor of all-cause mortality and poor outcomes in patients with acute ischemic stroke [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The association between the TyG index and carotid plaques has been demonstrated in many studies [8][9][10][11][12][13]. The TyG index was positively associated with an elevated risk of carotid plaque prevalence [8,9,11,13] and incidence [10,12] in the general population. Consistent with previous studies, our results showed that a high TyG index was positively associated with carotid plaques and metabolic components such as obesity, high BP, low HDL cholesterol, high triglycerides and high glucose levels.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, the TyG index has been considered an accessible and convenient measurement for estimating insulin resistance [32] and may be useful for predicting CVD events in clinical practice [33,34]. The association between the TyG index and carotid plaques has been demonstrated in many studies [8][9][10][11][12][13]. The TyG index was positively associated with an elevated risk of carotid plaque prevalence [8,9,11,13] and incidence [10,12] in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation